PENENTUAN PEMILIHAN SUPPLIER DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) DI ASTON JAMBI HOTEL & CONFERENCE CENTER: Decision Support System (DSS), Supplier, Simple Additive Weighting (SAW), Delphi 7.0, MySql - Kahar, Novhirtamely; -, Nurhayati (LP2M Universitas Nurdin Hamzah, 2019)
In the current era of Industrial technology development, especially information technology, requires fast and accurate information in its implementation. Determination of supplier selection with a decision support system is one of the implementation of industrial technology developments. This study aims to build a Decision Support System (DSS) application for Determining Supplier Selection at the Aston Jambi Hotel & Conference Center by applying the Simple Additive Weighting (SAW) method. The SAW method is a weighted addition method, which is the weighted sum of the performance rating on each alternative on all criteria. The criteria used in the SPK for determining supplier selection are based on 6 (six) aspects of assessment, namely price, quality, payment, delivery accuracy, accuracy of quantity and distance. Supplier data, item data, alternative data, and criteria as input data. The results of this study are to produce a ranking sequence of suppliers that have been selected and the output of the application can help make decisions in selecting suppliers according to predetermined criteria. The application in this study was implemented using the Borland Delphi 7.0 Programming Language and the database using MySql.